A new species of the genus Apteroloma Hatch, 1927 (Coleoptera, Agyrtidae) from China - Jiang, Ri-Xin; Zhang, Hong-Rui; Wang, Shuo (Zootaxa, 2021)
A new species of the genus Apteroloma Hatch, 1927 is described from China: Apteroloma qiului sp. nov. from Hubei Province. Habitus and diagnostic features of the adult are described and illustrated.